Association Between Maternal Nutritional Status During Pregnancy and Infant Birth Weight: A Cross-Sectional Study - Amina Ahmad; Nur Ekawati; Nelly Nugrawati (Jurnal Ilmu Kesehatan Nusantara, 2025)
Background: Maternal nutritional status during pregnancy plays a fundamental role in fetal growth and is a major determinant of infant birth weight. Poor maternal nutrition increases the risk of low birth weight (LBW), which remains a significant public health concern due to its association with neonatal morbidity, mortality, impaired growth, and long-term health complications. Understanding the relationship between maternal nutritional status and birth weight is essential for strengthening maternal and child health interventions. Research Objective: This study aimed to determine the association between maternal nutritional status during pregnancy and infant birth weight in the working area of the Tamalanrea Community Health Center, Makassar. Methods: A quantitative study with a cross-sectional design was conducted in July 2025. The study included 25 mothers selected through purposive sampling. Secondary data were obtained from maternal and child health records and medical records at the Tamalanrea Community Health Center. Maternal nutritional status was categorized as good or poor, while infant birth weight was classified as normal birth weight or low birth weight. Descriptive statistics were used for univariate analysis, and the Chi-square test was performed to assess the association between variables at a significance level of p < 0.05. Results: Among the respondents, 60.0% had good nutritional status, while 40.0% had poor nutritional status. Most infants (68.0%) were born with normal birth weight, whereas 32.0% had low birth weight. The Chi-square analysis revealed a statistically significant association between maternal nutritional status and infant birth weight (p = 0.021). Mothers with poor nutritional status were more likely to deliver low birth weight infants than mothers with adequate nutritional status. Conclusion: Maternal nutritional status during pregnancy is significantly associated with infant birth weight. Strengthening nutritional screening, nutrition education, and routine antenatal care is essential to improve maternal nutritional status and reduce the incidence of low birth weight.